Evaluation of some overlapping and differences between the Shahnameh, Jamshid Garshasbnameh and working on a Fereydoun, Mazandaran . . . - عباس شنکایی; کاظم دزفولیان; مجتبی دماوندی (تاریخ ادبیات)
At the end of the Sassanian era and the early Islamic period, ancient history has been written and has taken it out of oral form and has been called it “Khoday name”. Since, these documents were boring, and out of print, people like Ferdowsi brought it to poetry and add it elegance and literary industries and gave them a very nice atmosphere. Fifth and sixth-century epic poets put Ferdowsi as their model and his defects were completed with other epic one. Wherever they encountered something wrong in Shahnameh or saw an expression needed to explain, with respect to Ferdowsi, issues were resolved. In this paper, we have examined the books “Garshasb name” and “Kush name” which written by “Asadi Toosi” and “Iranshah-ibn-Abilkheir”. In these books, Ferdowsi differences about “Jamshid”, “Barmayen”, “Dive Sefid”, and “Mazandaran” was expressed in very pleasant manner.